Implementation evaluation of cocoa hand pollination program in Ghana - Asirifi, Solomon; Amankwah, Kwadwo; Ankuyi, Fred; Tham-Agyekum, Enoch Kwame; Akowuah, Addison Kwasi; Oduro-Owusu, Akua Yeboah; Amoako, Prince Kwadwo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The study examines the Cocoa Hand Pollination Program (CHPP) and its potential to revolutionize cocoa farming in Ghana's cocoa industry. The study employed an exploratory research design, collecting primary data through structured questionnaires from 367 cocoa farmers, 159 pollinators, and 30 extension staff. Data were analyzed descriptively. The study revealed that cocoa farmers have a relatively low level of knowledge about CHPP's objectives but perceive these goals as highly important. Farmers have successfully increased cocoa yield per hectare but face challenges in boosting overall cocoa production. Farmers exhibit a good understanding of CHPP activities and consider them crucial for program success. Pollinators have successfully enhanced natural pollination but are less positive about their contributions to socioeconomic livelihood improvement and entrepreneurship skills. Extension staff perceive the program as successful in helping farmers increase yield per hectare. However, the goals of integrating hand pollination into routine GAP activities have faced challenges. The efforts and goals of CHPP are generally valued by extension administrators who are committed to the program. Organizational and community characteristics generally favoured the program, but there were inconsistencies in the timely delivery of essential tools. This study offers valuable insights into the program's challenges and opportunities, providing essential information for policymakers and researchers working to improve cocoa production, uplift farmer livelihoods, and address similar agricultural contexts. Addressing challenges, enhancing knowledge sharing, and optimizing program elements can ensure cocoa farming's long-term sustainability and success, benefiting local farmers and the cocoa industry as a whole